Go, dog, go! - Eastman, P. D. (Philip D.) (New York : Beginner Books, 1961)
A story for beginning readers about busy dogs of all sizes and colors, engaged in all manner of silly activities.
K-3
240L
E
1.4
Keywords: Dogs -- Fiction; Humorous stories; Readers (Elementary)